The Mechanical Properties of Concrete Containing of Eggshell (0%, 5%, 10% and 15%) as Replacement Material by Using Simulation of Abaqus Method. - ABDULLAH, MOHD SUFYAN; Long Bongsu, Long Muhammad Najmuddin (Progress in Engineering Application and Technology, 2020)
Abstract: Eggshell is classified as a waste material by the food industry in any countries. Unfortunately, it is in fact eggshell appertain in highly sophisticated composite and have poor degradable waste. Therefore, identification of suitable percentage of eggshell as a substitute of aggregate in making concrete is necessary to conduct as recycling eggshells into the useful product gives good potential benefit on controlling food waste and construction industry. This study focusses on the mechanical properties of concrete containing of eggshell of concrete. The normal concrete mix consist of basic constituent such as Portland cement, fine and coarse aggregate, and water were considered as a control mix without addition of ESA that means it consists of 0% of ESA. Three series of concrete mix design with ESA as cement replacement were composed as an unconventional mix consist of 5%,10% and 15%. This result will be done by using Abaqus method. This software was to analyze the compressive strength of the concrete by using Abaqus method.